DOA/MoM-based ABF algorithm for SINR enhancement - Dawood, Heba S; Hussein, Amr Hussein; Gemeay, Entesar; Attia, Mahmoud Ahmed (IET communications, 2019)
In this study, a new non-iterative adaptive beamforming (ABF) algorithm for the signal-to-interference and noise ratio (SINR) enhancement is proposed. It is based on a combination between the direction of arrival (DOA) estimation and the method of moments (MoM). The proposed algorithm is denoted as DM/ABF which stands for DOA and MoM-based ABF. The DOA is used to provide accurate estimates for the directions of the desired and interfering signals. On the basis of the estimated DOAs, a dedicated shaped pattern version of the ordinary pattern is created and applied as the desired input to the MoM algorithm. The MoM is used for shaped pattern synthesis to estimate the weights vector required to provide deep nulls toward the interfering signals and directs the main beam toward the desired signal. In this case, the weights vector does not update iteratively at each received signal sample as in case of least mean square (LMS) and recursive least squares (RLSs) algorithms, but it is updated only when the estimated DOAs of the desired and interfering signals are changed. Furthermore, a large number of close nulls can be produced without the need for additional antenna elements compared with other algorithms.